Análisis de la gestión de almacenamiento de la bodega principal de productos terminados: caso de productos de consumo de masivo - Cruz B., Cristina (2010)
Inventories are necessary in every company, because they give the firm time to react to the inaccuracy of forecasts, both in sales and production or supply chain Consumer needs are constantly evolving, generating the creation and accumulation of Skus. This paper defines guidelines for efficient storage management of a main warehouse of finished products of an industrial partner. This firm is dedicated to the production and marketing of consumer products. This thesis proposes the following solutions to improve warehouse management: The evaluation of rotation and coverage indexes, the ABC analysis of products in order to determine the most appropriate location for the product according to it's gates of entry and exit and also, the proper storage standards according to the type of product. As a result, an orderly and organized location of products was obtained, as well as the definition of a picking area and 8 enabled platforms for receiving and dispatching; which in consequence provided an optimal configuration in the layout of the warehouse, keeping the Skus that added value to minimize the time of dispatch and reception, thus generating cost savings.